Home wireless networking in a snap - Habraken, Joseph W., 1954- (Sams teach yourself., 2006)
These days, nobody really wants to learn everything there is about their hardware and software. And even if you did, who has the time to endlessly tinker and play with it until you figure everything out? You just want a book that will quickly show you how to set up your home wireless network. Home Wireless Networking in a Snap is designed specifically for busy people like you. This book covers the things that aren't already covered in the documentation that came with your equipment and the things you can't just figure out on your own. It is organized into a series of well-organized, bite-sized, quickly accomplished tasks, that lets you zero right in on particular tasks you want to accomplish. This hands-on approach to setting-up a secure home wireless network will have your network up and running in no time.